Is growth rate more important than survival and reproduction in sheep farming in Ghana? (Journal of Science and Technology, 2016)
The local Djallonké sheep in Ghana is characterized by slow growth and low reproductive rates, but is resistant to most diseases and parasites (survival traits). In an attempt to improve the performance of the local sheep, the Ministry of Food and Agriculture has chosen growth rate as the breeding objective. This is being achieved through the Open Nucleus Breeding Scheme, with the Ejura Sheep Breeding Station being the nucleus farm. The objective of this work was to find out which of the three traits (survival, growth rate and reproduction) is worth including in the breeding objective in the sheep breeding scheme in Ghana. The study was carried out at Ejura Sheep Breeding Station. The methodused to compare the three traits involved calculating the economic values of the three traits by using computer models. The economic value of a trait was defined as the marginal profit per ewe per year resulting from a unit increase or decrease in the average value of a trait, whilst holding the average levels of all other traits constant, and at a discount rate of 0 and 12.5%. The results of the study indicated that on average, traits associated with survival had the highest average discounted (12.5% over the lifetime of the breeding ewe-5.6667 years) economic value (¢3330.04 or $0.36). This was followed by reproduction (¢1944.72 or $0.21) with growth rate recording the lowest average discounted economicvalue of ¢703.96 or $0.08. This means that the order of importance of the three traits with respect to profit maximization in the sheep industry is survival > reproduction > growth rate. It was concluded that all three traits (survival, reproduction and growth rate) should be included in the breeding objective of the sheep breeding scheme in Ghana, instead of concentrating only on growth traits.